Synthesis of Lactic Acid from Molasses by Lactobacillus acidophilus Using a Batch Fermentation Process - Rahmayetty, Rahmayetty; Yulvianti, Meri; Hartono, Rudi (Jurnal Rekayasa Kimia & Lingkungan, 2022)
Lactic acid is a chemical with widespread applications, mainly in pharmaceutical, cosmetic, chemical as well as food industries. One of the major uses of lactic acid is the polylactic acid (PLA) feedstock which is biodegradable and biocompatible as an alternative to plastic derived from fossil fuels. Efforts continue to be made to reduce the cost of producing PLA in order to compete with the conventional petrochemical-based plastics. This include the use of molasses as a raw material because it is cheap and contains high glucose. The purpose of this study was to obtain cell concentrations through the addition of starter volume that produces high concentrations of lactic acid and to obtain the growth kinetics of Lactobacillus acidophilus during the fermentation process. This study was conducted in several stages; the design of bioreactors, inoculation of Lactobacillus acidophilus, and fermentation of molasses. In a batch system, molasses substrate was directly inserted as much as 500 ml in the fermentor and the addition of starter volume of Lactobacillus acidophilus was 1; 3; 5 dan 10% v/v. The fermentation of molasses for 72 hours and the product was analysed every 8 hours. The highest concentration of lactic acid produced in batch fermented molasses was added to 5% (v/v) starter volume with 72 hours of fermentation time, which was 23.1 mg/L, with value the carrying-capacity coefficient (k) and the maximum net specific growth rate (net) were 0.2379 h-1 and 0.0160 h-1 respectively.